Mosaicplasty Technique in the Treatment of Isolated Knee Femoral Condyle Osteochondral Lesions - a Retrospective Study - Samir Karmali; Rui Guerreiro; Daniel Sá da Costa; Jorge Fonseca; Ricardo Gonçalves (Revista Brasileira de Ortopedia)
Abstract Objective Focal osteochondral lesions of the knee are found in two thirds of patients undergoing arthroscopy; their treatment, when isolated and especially in young individuals, remains a debating topic. The present study analyzes the results obtained by the application of the mosaicplasty technique on the treatment of isolated knee femoral condyle osteochondral lesions. Methods Retrospective study of patients submitted tomosaicplasty and to subjective analyseswith pre- and postsurgery International KneeDocumentation Committee (IKDC) scores. Results A total of 13 cases with an average age of 34 years old, with male patients (n = 4; 31%) with an average age of 23 years old (range: 17-31 years old), and female patients (n = 9; 69%) with an average age of 39 years old (range: 16-56 years old); medial versus lateral femoral (n = 11; 85% versus n = 2; 15%); the average size of the lesion was 1.8 cm2 (range: 0.6-4 cm2); average follow-up time: 5.045 ± 3.47 years (range: 1.15-11.01 years). The average preoperative IKDC score was of 31.63 points (± 20.24), the average postoperative IKDC score was of 74.18 points (± 20.26). The difference between the post- and preoperative IKDC scores was of 42.55 (± 21.05) points, being theminimal score increase of 8.1 points andthemaximumscore increaseof82.8 points.Astatistically significant difference (p < 0.001) was found between the IKDC scores before and after the surgery. A statistically significant relation (p = 0.038) was found between the IKDC score increase (the difference between the postoperative and the preoperative scores) and the dimension of the lesion. Conclusions Mosaicplasty with osteochondral autograft transfer, when adequately used, can produce excellent results with great durability and functional impact, low morbidity rates and costs. Expansion of the indication criteria shows promising midterm and long-term results.